An Evaluation of Seasonal Maternal-Neonatal Morbidity Related to Trainee Cycles. Issue 12 (December 2022) - Oben, Ayamo; McGee, Paula; Grobman, William A.; Bailit, Jennifer L.; Wapner, Ronald J.; Varner, Michael W.; Thorp, John M.; Caritis, Steve N.; Prasad, Mona; Saade, George R.; Rouse, Dwight J.; Blackwell, Sean C.
Abstract : (Abstracted from Am J Obstet Gynecol MFM 2022;4:100583) The "July phenomenon" is the concept that the arrival of new physicians into clinical practice around July corresponds with the deterioration of patient outcomes. In addition, around this same time frame, those in residency also gain new levels of responsibility that require training.